Detección de Leptospira spp. en cuyes de la parroquia Chuquiribamba del cantón Loja - Quizhpe Criollo, Claudia Stefania (2024)
Leptospirosis is an infectious disease caused by pathogenic bacteria of the genus Leptospira which is spread through the urine of infected animals. This disease represents a global public health challenge, affecting both developing and developed countries. In production animals, such as cattle, it can cause problems such as abortions, infertility, mummification, increased neonatal mortality and decreased production, resulting in significant economic losses. In the present observational cross-sectional study, pathogenic Leptospira was detected by conventional PCR (hap1 gene) in 85 guinea pigs from Chuquiribamba parish from urine samples, and antibodies were also detected in animals eliminating the bacterium by serology by MAT (OIE, 2021). Two PCR positive animals were detected (2,35%) but one of these samples was negative in TMA. This finding evidences the need to monitor the disease especially in domestic animals, allowing to suggest adequate control measures to reduce the risk of infection in animals and humans as accidental susceptible species.